2016
DOI: 10.1007/s12306-016-0397-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of medial patello-femoral ligament reconstruction: comparison between a double-bundle converging tunnels technique versus a single-bundle technique

Abstract: This study is the first biomechanical evaluation of the MPFL reconstructions in natural orientation. Both the procedures achieved safe fixation of the graft at the femoral attachment; however, the single-bundle technique reported 11 % of failure at the patellar side due to patellar fracture. In addition, the double-bundle technique can better restore the anatomy of the native ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
(35 reference statements)
1
18
1
3
Order By: Relevance
“…While some studies have observed increased rates of postoperative patellar fracture after the use of bone tunnels for graft fixation, there has been a trend toward techniques that avoid utilization of tunnels. 15 , 35 Finally, our analysis also found that postoperative infections requiring surgical intervention are a rare (1.2%) complication after patellar instability surgery, which is consistent with previous studies. 33 , 38 , 49 …”
Section: Discussionsupporting
confidence: 91%
“…While some studies have observed increased rates of postoperative patellar fracture after the use of bone tunnels for graft fixation, there has been a trend toward techniques that avoid utilization of tunnels. 15 , 35 Finally, our analysis also found that postoperative infections requiring surgical intervention are a rare (1.2%) complication after patellar instability surgery, which is consistent with previous studies. 33 , 38 , 49 …”
Section: Discussionsupporting
confidence: 91%
“…11 18 The graft configuration with two separate bundles at the patella is more anatomical, reduces the risk of patellar fracture, presents a lower incidence of new dislocations, and increases functional scores compared with single bundles. 25 26 We have decided to perform the reconstruction with a single patellar tunnel and a free flexor tendon graft in order to avoid damage to the knee extensor apparatus and to reproduce the anatomical path of the graft deep to the vastus medialis fascia. Another disadvantage is the location of the origin of the patellar tendon in the anterior and inferior surfaces of the patella, which is a nonanatomic MPFL point, besides the lateral inclination of the collagen fibers in the tibial tuberosity, which would hamper the original vector of action forces for medial patellar containment in cases of surgical reconstruction with this graft repositioned to the medial side of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…11 18 A configuração do enxerto com dois feixes separados na patela é mais anatômica, diminui o risco de fratura da patela, apresenta menor incidência de novas luxações e adiciona mais pontos nos questionários funcionais em comparação com o feixe único. 25 26 Optamos pela reconstrução com túnel único na patela e enxerto livre dos tendões flexores para não lesionar o aparelho extensor do joelho e também para reproduzir o trajeto anatômico do enxerto profundamente a fáscia muscular do vasto medial. Outro aspecto desfavorável que ressaltamos está relacionado à localização da origem do tendão patelar na face anterior e inferior da patela, que é um ponto não anatômico do LPFM, além da inclinação lateral das fibras colágenas na tuberosidade da tíbia, o que dificultaria a ação original do vetor de forças para contenção medial da patela, no caso da reconstrução cirúrgica com esse enxerto reposicionado para o lado medial do joelho.…”
Section: Discussionunclassified
“…Out of the 130 various methods of MPFL reconstruction, the Double Bundle Procedure is the most commonly used as it provides a larger degree of pain-free range of motion [5][6][7][8]. Locating the exact drilling location on the medial aspect of the patella and the medial femur is a challenge for the surgeon and literature suggests that the current procedure leads to non-anatomical placement of the ligament [9].…”
Section: Introductionmentioning
confidence: 99%